Role of up-regulation of oxidative stress biomarkers in thrombotic transformation of atherosclerotic plaque in Acute Coronary Syndrome (ACS) patients from a lower middle income country - Aamenah Malik, Huma Sattar, Arif Malik, Rukhshan Khurshid, Awais Altaf, Maira Mahmood, Mariam Malik, Farhat Ijaz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In response to oxidative stress, reactive oxygen species aggravate and activate different signaling mechanism and stimulate the release of different inflammatory mediators, and provoke the generation of oxidative stress, all of which can promote the development of acute coronary syndrome. Methodology: The study sample comprised of 76 ACS patients and 76 healthy controls. Blood samples of ACS patients and controls were collected to determine the serum concentration of antioxidants, and the serum levels of inflammatory biomarkers. Spectrophotometric method and ELISA kit method was used to measure these variables accordingly. Results: The results indicated a significant rise in the levels of IL-1, IL-6, IL-8, TNF-α, MMP-11, ICAM-1 and VCAM-1 in ACS patients compared to controls whereas significant decrease was recorded in GSH, CAT, SOD, GRx and HDL levels in patients with ACS compared to controls. Conclusion: The present study indicated that the increased serum concentration of inflammatory cytokines and antioxidant reduction may influence the pathogenesis of ACS.